Quantum cascade lasers with an integrated polarization mode converter - Dhirhe, D.; Slight, T.; Holmes, B.; Hutchings, D.; Ironside, Charlie (2012)
We discuss the design, fabrication and characterization of waveguide polarization mode converters for quantum cascade lasers operating at 4.6 µm. We have fabricated a quantum cascade laser with integrated polarization mode converter that emits light of 69% Transverse Electrical (TE) polarization from one facet and 100% Transverse Magnetic (TM) polarization from the other facet. © 2012 Optical Society of America.